Sampling Designs for Monitoring Ichthyoplankton in the Estuary Area: A Case Study on Coilia mystus in the Yangtze Estuary - Long, Xiangyu; Wan, Rong; Li, Zengguang; Wang, Dong; Song, Pengbo; Zhang, Fan (Frontiers in Marine Science, 2022)
Fishery-independent survey can provide detailed information for fishery assessment and management. However, sampling design for survey on ichthyoplankton in estuary area is still poorly understood. In this study, we developed six stratified schemes with various sample sizes, attempting to find cost-efficient sampling designs for monitoring Coilia mystus ichthyoplankton in the Yangtze Estuary. The generalized additive model (GAM) with Tweedie distribution was used to quantify the “true” distribution of C. mystus eggs and larvae, based on the data from fishery-independent survey in 2019-2020. The performances of different sampling designs were evaluated by relative estimation error (REE), relative bias (RB) and coefficient of variation (CV). The results indicated that appropriate stratifications with intra-stratum homogeneity and inter-stratum heterogeneity could improve precision. The stratified schemes should be divided not only between north and south branch, but between river and sea. No less than two stratifications in south branch could also get better performance. The sample sizes of 45-55 were considered as the cost-efficient range. Comparing to other monitoring programs, monitoring ichthyoplankton in estuary area required a more complex stratification and a higher resolution sampling. The design ideology and optimization methodology in our study would provide references to sampling designs for ichthyoplankton in estuary area.